Pengaruh kombinasi Fe dan Co terhadap pertumbuhan Chlorella sp. dan penyisihan COD limbah cair minyak sawit - Shinta Elystia; Indah Kartika Zulfa; Sri Rezeki Muria (Dinamika Lingkungan Indonesia, 2020)
Palm oil mill effluent contains pollutants and has high content of organic matter. The treatment process of palm oil mill effluent generally with open pond system that requires extensive land and a long contact time. To reduce the number of ponds needed in the process of palm oil mill effluent, microalgae Chlorella sp. by using palm mill effluent which contains organic material as a source of nutrition for microalgae cultivation media Chlorella sp. to improve the efficiency of COD removal in palm oil mill effluent. In this research, variations of the concentration of Fe and Co micronutrients were combined with variations concentrations of Fe (0.3; 0.5 and 0.7) mg/L and Co (1 and 2) mg/L in flat-photobioreactors were carried out for 7 days with lighting by using sunlight. The results showed that at a combination of 0.5 mg/L Fe + 0.2 mg/L Co, the highest microalgae cell growth was 6 x 106 cell/ml and the highest removal efficiency of COD was 83.3%.